Effects of exercise load and blood-flow restriction on skeletal muscle function - Cook, S. B.; Clark, B. C.; Ploutz-Snyder, L. L. (Medicine & Science in Sports & Exercise, 2007)
Resistance training at low loads with blood flow restriction (BFR) (also known as Kaatsu) has been shown to stimulate increases in muscle size and strength. It is unclear how occlusion pressure, exercise intensity, and occlusion duration interact, or which combination of these factors results in the most potent muscle stimulus.